ATI1 (ATG8-interacting protein 1) and ATI2 define a plant starvation-induced reticulophagy pathway and serve as MSBP1/MAPR5 cargo receptors. Issue 11 (2nd November 2021) - Wu, Jian; Michaeli, Simon; Picchianti, Lorenzo; Dagdas, Yasin; Galili, Gad; Peled-Zehavi, Hadas
ABSTRACT: Reticulophagy, the selective autophagy of endoplasmic reticulum (ER) components, is known to operate in eukaryotes from yeast and unicellular algae to animals and plants. Thus far, only ER-stress induced reticulophagy was reported and analyzed in plants. In this study we characterize a reticulophagy pathway in Arabidopsis thaliana that is triggered by dark-induced starvation but not by ER stress. This pathway is defined by the previously reported ATG8-interacting proteins, ATI1 and ATI2. We further identified the ER-localized MSBP1 (Membrane Steroid Binding Protein 1) as an ATI1- and ATI2-interacting protein and an autophagy cargo, and show that ATI1 and ATI2 serve as its cargo receptors. Together, these findings expand our knowledge on plant responses during energy deprivation and highlight the role of this special type of reticulophagy in this process. Abbreviations : AGO1: ARGONAUTE 1; ATI: ATG8-Interacting Protein; BiFC: Bimolecular Fluorescence Complementation; BR: brassinosteroid; conA: concanamycin A; DMSO: dimethyl sulfoxid; DTT: dithiothreitol; ER: endoplasmic reticulum; GFP: green fluorescent protein; MAPR: Membrane-Associated Progesterone Binding Protein; MSBP: Membrane Steroid Binding Protein; SD: standard deviation; SE: standard error; TM: tunicamycin; TOR: target of rapamycin; Y2H: yeast two-hybrid.